Improving nutrition as a development priority: Addressing undernutrition in national policy processes in Sub-Saharan Africa - Benson, Todd (International Food Policy Research Institute, 2008)
In sum, it is crucial to alter the perception that undernutrition is part of the normal order of things. Advocacy groups should generate a perception of crisis related to undernutrition in order to foster significant, urgent, high-profile action by government. Although a perception of nutritional crisis cannot be sustained in the long term, it should be possible to exploit incremental changes in the perception of the undernutrition issue to promote more effective actions to assist the undernourished. Given that undernutrition is a solvable problem that, in part, requires public action, governments can and should be held accountable for the persistent presence of undernourished women and children in the population, the unnecessary suffering that they experience, and the limited potential that they have to live long, healthy, productive, and creative lives.